Anticorpos para Leptospira spp., Toxoplasma gondii e Neospora caninum em cães errantes albergados em canil privado - Goncalez, C. C. [UNESP]; Paes, Antonio Carlos [UNESP]; Langoni, Hélio [UNESP]; Da Silva, R. C. [UNESP]; Greca, H. [UNESP]; Camossi, L. G. [UNESP]; Guimaraes, F. F. [UNESP]; Ullmann, L. S. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2010)
The serological profile of 300 mongrel dogs of various ages and gender were investigated. Animals were captured in the streets and afterwards directed to a private kennel in Avare city (SP) to search for leptospirosis, toxoplasmosis, and neosporosis. Blood samples were obtained from jugular or cephalic vein for the obtention of sera. The microscopic agglutination test (MAT) was used to leptospirosis. MAT detect the prevalence of 9.3%. The most frequent reactant serovars were Bratislava (35.7%), Cynopteri (17.9%), Autumnalis (14.3%), and Copenhageni (10.7%), besides 7.1% to others serovars: Icterohaemorrhagiae, Canicola, and Hardjo. The modified agglutination test used for the diagnosis of toxoplasmosis showed 26% of positive animals, with titers varying from 16 to 256, with 16 in 3.3%, 64 in 13.7%, and 256 in 9% of the samples. To canine neosporosis, it was used the indirect fluorescent antibody test, and two animals (0.7%) demonstrated antibodies with titers 25 and 100. The results show the participation of the animals in the epidemiological chain of the researched diseases.
Antibodies to Leptospira spp., Toxoplasma gondii, and Neospora caninum in mongrel dogs kept in private kennel
Keywords: dog; leptospirosis; toxoplasmosis; neosporosis; serology